Takaful program: Giving Egypt’s poor a hand up, not just a handout - Karachiwalla, Naureen; Gilligan, Daniel O.; Kurdi, Sikandra (CGIAR System Organization, 2024)
In many low- and middle-income countries, social protection programs such as cash transfers are seen as essential tools for alleviating poverty. Egypt’s Takaful program, launched in 2015, is a flagship example, targeting poor households with monthly cash transfers to improve their well-being. While cash transfers are increasingly popular and being scaled up globally, their effectiveness is often debated—especially when it comes to their short-, medium,- and long-term impacts.